Edukasi Penggunaan Bahan Tambahan Pangan untuk Menjamin Keamanan Pangan Olahan KWT Harapan Jaya Bandar Lampung - Chandra Utami Wirawati; Henry Kurniawan; Irmayani Noer; Ni Siluh Putu Nuryanti; Nurbani Kalsum (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Food additives application in food processing should be a conscious matter by either producers or consumers due to food additives excessive and misuses that will give negative impact on human well-being. Farmer Women Group (FWG) Harapan Jaya Rajabasa is one of small and medium enterprises (SMEs) engaged in beverage processing, especially soy milk and herbal ginger drinks. These product marketing was still limited to local area, nevertheless consumer demands and auction for both products were quite effective for family additional income and support family food security. Food additives awareness to the member of Harapan Jaya FWG in food processing become an important factor in production process sustainability not only to improve the product selling but also as an assurance in food safety for their own family members that consumed the product. The method used is counseling and demonstration followed by evaluation. The activity was attended by 22 FWG members. The activity was preceded by brain storming the FWG members awareness on food additives application in food products. Most of the KWT members (more than 84%) have not notice for the regulation, type of food additives, dosage and how to applied food additives in food product. The evaluation results showed that FWG’s member awareness and good practice in food additives regulation, type and dosage, and method to applied had increased.